Rancang Bangun Aplikasi Inventaris Aset Berbasis Android - Vera Alviani; Nurkhalik Wahdanial Asbara; Magfira Tunnisa (JURIKOM (Jurnal Riset Komputer), 2022)
This school asset inventory application is used to monitor the cycle of borrowing and returning equipment so that there is no loss of equipment that results in losses to the school. The waterfall method is a process of developing a device or system sequentially, this method is used to monitor the cycle of borrowing and returning school inventory where progress is seen as a waterfall that continues to flow down through several stages. Testing this system uses the blackbox testing method to test the implementation of the running system. The results of the study produced a mobile application that allows mobility with certain equipment, mobile applications can facilitate other activities or work